2011
DOI: 10.1039/c1ee01240a
|View full text |Cite
|
Sign up to set email alerts
|

The current status of hydrogen storage in metal–organic frameworks—updated

Abstract: Hydrogen storage in metal-organic frameworks (MOFs), or porous coordination polymers, has been extensively investigated in the last two years and this review is to serve as an up to date account of the recent progress. The effects of MOF sample preparation and activation, functionalization (including post-synthetic), catenation, unsaturated metal sites, metal doping and spillover have been discussed using recent examples. In addition to a condensed reference table of all recently reported MOFs for hydrogen sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
252
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(265 citation statements)
references
References 171 publications
(153 reference statements)
9
252
0
4
Order By: Relevance
“…Recently, a MOF denoted as either PCN-69 27 or NOTT-119 28 with the rht topology was synthesized by both the Zhou and Schroder groups. PCN-69/ NOTT-119 has a Brunauer−Emmett−Teller (BET) surface area of ∼4000 m 2 /g and is made from the phenyl-based strut LH 6 (1) (Scheme 1). Even though LH 6 (1) is longer than LH 6 (2), the strut used to make NOTT-112 26 (3800 m 2 /g), the surface area of PCN-69/NOTT-119 did not increase significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a MOF denoted as either PCN-69 27 or NOTT-119 28 with the rht topology was synthesized by both the Zhou and Schroder groups. PCN-69/ NOTT-119 has a Brunauer−Emmett−Teller (BET) surface area of ∼4000 m 2 /g and is made from the phenyl-based strut LH 6 (1) (Scheme 1). Even though LH 6 (1) is longer than LH 6 (2), the strut used to make NOTT-112 26 (3800 m 2 /g), the surface area of PCN-69/NOTT-119 did not increase significantly.…”
mentioning
confidence: 99%
“…Thus, six linked alkynes would replace two linked phenyl groups. Given the synthetic challenge presented by the corresponding trigonal linker, however, we chose instead to start by replacing each phenyl spacer in LH 6 (1) by one carbon−carbon triple bond.…”
mentioning
confidence: 99%
“…MOFs have been of interest due to their applications in gas storage/separation and catalysis as well as their photoluminescence and magnetic and electrical properties. [20][21][22][23][24][25][26][27][28] Interest in ferroelectric and subsequently multiferroic MOFs stems from work by Okada and Sugie 29 who synthesized Cu(HCOO) 2 .4H 2 O and discovered it to be antiferroelectric, the first instance of such behavior in a MOF. Suzuki and Okada 30 subsequently showed that there may be a temperature range below this transition where the compound becomes ferrielectric.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their syntheses can be carried out under mild conditions, allowing for their rational design and facile pre-and post-synthetic modification. 2 While some MOFs display extraordinary high hydrogen uptake at cryogenic temperatures, as a result of the generally low enthalpy of hydrogen adsorption (ca. 2-8 kJ mol -1 ) 2-4 being considerably lower than the ideal adsorption enthalpy allowing for ambient-temperature hydrogen storage, 15-25 kJ mol -1 , 5,6 their hydrogen capacity is practically negligible near ambient conditions; a serious drawback for application.…”
Section: Introductionmentioning
confidence: 99%